Facilitating shared decision-making with breast augmentation patients: Acceptability of the PEGASUS intervention. Issue 2 (February 2017) - Paraskeva, Nicole; Clarke, Alex; Grover, Rajiv; Hamilton, Stephen; Withey, Simon; Harcourt, Diana
Summary: Background: PEGASUS is an intervention to facilitate shared decision-making by helping prospective patients consider their expectations of surgery, so that surgeons have a clear understanding of their individual goals. To date, shared decision-making interventions within aesthetic surgery are lacking. The present mixed methods study therefore explored the acceptability of implementing PEGASUS into routine private practice with breast augmentation patients and aesthetic providers. Method: Seventeen women presenting for breast augmentation surgery from three practices received the PEGASUS intervention pre-operatively and completed a process evaluation post-operatively. Semi-structured interviews exploring 3 aesthetic providers' experiences of using PEGASUS were subjected to a thematic analysis, whilst a content analysis was conducted on the 77 goals identified by patients. Results: The majority of patients reported that the PEGASUS intervention was relevant, helpful and useful, and they felt comfortable during it. Qualitatively, patients and aesthetic providers found that PEGASUS enabled them to reflect on and discuss about their expectations from surgery. Aesthetic providers discussed some of the issues and barriers associated with implementing PEGASUS in routine private practice, factors that must be considered prior to further evaluation. Conclusion: This study provides preliminary support for the acceptability of PEGASUS to breast augmentation patients and to aesthetic providers working in the private sector.